Female puberty : a comprehensive guide for clinicians - Dietrich, Jennifer E. (Springer New York, 2014)
Female Puberty: A Comprehensive Guide for Clinicians is a practical reference, covering the full range of issues related to pubertal development.  Developed to answer pointed clinical questions and to provide a thorough review of the literature, the book covers both the basics and the complexities of puberty, encompassing psychosocial development to pubertal nuances in highly specialized populations.  Comprehensive in scope, this title offers concepts that are concisely conveyed and chapters that complement each other well.  Complex subjects such as details of the hypothalamic-pituitary-ovarian axis are covered in a readily understandable manner, and bullet points throughout the text serve as helpful reminders to the reader.  An invaluable contribution to the literature, Female Puberty: A Comprehensive Guide for Clinicians will be of great interest to all health providers concerned with female reproductive health - including obstetrician gynecologists, reproductive endocrine specialists, pediatricians, pediatric specialists, family practitioners, and allied health professionals.